Education as a moderator of middle-age cardiovascular risk factor-old-age cognition relationships: testing cognitive reserve hypothesis in epidemiological study - Iso-Markku Paakko; Kaprio Jaakko; Lindgren Noora; Rinne Juha O; Vuoksimaa Eero (OXFORD UNIV PRESS, 2022)
Background: higher educational attainment and less midlife cardiovascular risk factors are related to better old-age cognition. Whether education moderates the association between cardiovascular risk factors and late-life cognition is not known. We studied if higher education provides resilience against the deteriorative effects of higher middle-age body mass index (BMI) and a combination of midlife cardiovascular risk factors on old-age cognition.
Methods: the study population is the older Finnish Twin Cohort (n = 4,051, mean age [standard deviation, SD] = 45.5 years [6.5]). Cardiovascular risk factors and education were studied at baseline with questionnaires in 1975, 1981 and/or 1990 (participation rates of 89, 84 and 77%, respectively). Cognition was evaluated with telephone interviews (participation rate 67%, mean age [SD] =73.4 [2.9] years, mean follow-up [SD] = 27.8 [6.0] years) in 1999-2017. We studied the main and interactive effects of education and BMI/dementia risk score on late-life cognition with linear regression analysis. The study design was formulated before the pre-defined analyses.
Results: years of education moderated the association between BMI with old-age cognition (among less educated persons, BMI-cognition association was stronger [B = -0.24 points per BMI unit, 95% CI -0.31, -0.18] than among more educated persons [B = -0.06 points per BMI unit, 95% CI -0.16, 0.03], Pinteraction < 0.01). There was a similar moderating effect of education on dementia risk score consisting of cardiovascular risk factors (P < 0.001).
Conclusions: our results support the cognitive reserve hypothesis. Those with higher education may tolerate the deteriorative effects of midlife cardiovascular risk factors on old-age cognition better than those with lower education.